(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
Extension, teaching and research are primary functions of the university. These missions should be interrelated in institutional policies to enrich each other. The Latin American extension is consolidated as a heterogeneous, multidimensional field and in permanent construction. The purpose of this article is to analyze the concept of extension that underlies the regulatory framework approved at UNLPam between 2010-2017. A survey of the regulations, the Statute and the strategic plans was carried out. The vision of extension, its academic recognition and the integration of the functions were analyzed. The study period can be considered key for extension at UNLPam; because an institutional and normative framework was agreed that led to its greater hierarchy. The foundations were laid to think about it from a critical perspective and from the integrality of the functions. This new scenario led to greater participation and appreciation of this mission.